Association between age‐related sensory impairment with sarcopenia and its related components in older adults: a systematic review. Issue 2 (1st March 2022) - Ho, Kam Chun; Gupta, Preeti; Fenwick, Eva K.; Man, Ryan E.K.; Gan, Alfred T.L.; Lamoureux, Ecosse L.
Abstract: Sensory impairments and sarcopenia are both highly prevalent age‐related conditions, with the former having been postulated to contribute to the pathogenesis of the latter condition. Confirming this hypothesis may therefore help to better inform strategies for early treatment and intervention of sarcopenia. We performed a systematic review of the current literature examining the relationships between four major sensory impairments [vision (VI), hearing (HI), smell (SI), and taste (TI)] with (i) sarcopenia; and (ii) its associated components (low handgrip strength, slow gait speed, and low muscle mass). PubMed, EMBASE, CINAHL, and Cochrane Library databases were searched for observational studies investigating the relationship of VI, HI, SI, and TI with sarcopenia, low handgrip strength, slow gait speed, and low muscle mass, in adults aged 50 years or older, from inception until 24 May 2021. The risk of bias of the included studies was assessed using the Newcastle‐Ottawa Scale. This study was registered with PROSPERO, reference CRD42021247967. Ten cross‐sectional and three longitudinal population‐based studies of community‐dwelling adults ( N  = 68 235) were included, with five studies investigating more than one sensory impairment. In total, 8, 6, 3, and 1 studies investigated the relationship between VI, HI, SI, and TI and sarcopenia and its related components, respectively. Follow‐up duration for the longitudinal studies ranged from 4 to 11 years. All studies had a low or moderate risk of bias. We found that the presence of VI and SI, but not TI, independently increased the odds of sarcopenia. In addition, VI and SI were each independently associated with low muscle mass; and VI, HI, and SI were each independently associated with slow gait speed. However, we found inconclusive evidence for the associations between VI, HI and SI, and low handgrip strength. Our systematic review suggests a potential association between the presence of single or multiple sensory impairments and a greater likelihood of sarcopenia and/or deficits in its associated components, especially for VI, HI, and SI. Prospective studies are needed to untangle the relationship between sensory impairment and sarcopenia to better inform clinical guidelines for disease prevention and management.